2022
DOI: 10.1002/marc.202100926
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Structures in Macromolecule‐Assembled Synthetic Cells

Abstract: Various models of synthetic cells have been developed as researchers have sought to explore the origins of life. Based on the fact that structural complexity is the foundation of higher‐order functions, this review focuses on hierarchical structures in synthetic cell models that are inspired by living systems, in which macromolecules are the dominant participants. The underlying advantages and functions provided by biomimetic higher‐order structures are discussed from four perspectives, including hierarchical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 119 publications
(200 reference statements)
0
5
0
Order By: Relevance
“…[59][60][61][62][63][64][65][66] Due to the dynamic modulation of the internal micro-environment, the internal compartments could be generated through liquid-liquid phase separation (LLPS), [49,50] which could be used to simulate the dynamic formation of membranelles organelles in living cells (Figure 3a). To date, different approaches, including diffusion of signaling molecule, [27,51,67] alteration of pH, [58,68] temperature or osmotic pressure, [34,36,[69][70][71][72][73][74] and light irradiation, [75][76][77][78][79] have been developed to regulate the dynamic LLPS process within a protocell.…”
Section: Dynamic Construction Of Hierarchical Protocellmentioning
confidence: 99%
See 1 more Smart Citation
“…[59][60][61][62][63][64][65][66] Due to the dynamic modulation of the internal micro-environment, the internal compartments could be generated through liquid-liquid phase separation (LLPS), [49,50] which could be used to simulate the dynamic formation of membranelles organelles in living cells (Figure 3a). To date, different approaches, including diffusion of signaling molecule, [27,51,67] alteration of pH, [58,68] temperature or osmotic pressure, [34,36,[69][70][71][72][73][74] and light irradiation, [75][76][77][78][79] have been developed to regulate the dynamic LLPS process within a protocell.…”
Section: Dynamic Construction Of Hierarchical Protocellmentioning
confidence: 99%
“…[69] The dynamic intracellular coacervate formation could also be regulated by altering environmental pH. [58,68] Last et al demonstrated that a step increase in pH in the external environment from 4 to 9 induced the deprotonation of the ATP molecule, which was pre-encapsulated in the lipid vesicle. The negatively charged ATP could form coacervate microdroplets with positively charged pLL within the protocell (Figure 3b).…”
Section: Dynamic Construction Of Hierarchical Protocellmentioning
confidence: 99%
“…Several reviews have already summarized fabrication and assembly techniques of modular tissue engineering [ 5 , 8 11 ]. In this review, we focus on applications of bioprinting in bottom-up tissue engineering, especially its capability of mimicking physiological complexity to form spatially organized tissues.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Particularly challenging in the context of synthetic cell engineering is the production of sufficiently complex and robust cell-like architectures containing multiple compartments that serve to localise, segregate, and regulate function and environment. 6,7 These enclosures are often membranebased, constructed from phospholipids and/or fatty acid vesicles, [8][9][10][11][12] polymersomes, 13,14 or proteinosomes, 15,16 but alternative membraneless architectures are emerging in the form of hydrogel capsules, coacervates, or synthetic condensates. [17][18][19][20][21] Microfluidics is a typical strategy for producing synthetic cell scaffolds, being particularly effective at generating monodisperse and nested structures in small quantities.…”
Section: Introductionmentioning
confidence: 99%